Improving Students' Reading Comprehension Through Pictures at SMA Negeri 1 Remboken - Harun, Meilani; Liando, Nihta V. F; Rorimpandey, Rinny S (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
This study sought to determine how to use pictorial posters as media to enhance students' reading comprehension. The study was carried out in SMA Negeri 1 Remboken's Grade XI-IPA. This study used a pre-experiment design employing a reading assessment. Pre-test, treatment, and post-test phases were all included in the data gathering process. 22 students in all were the sample for this study, and they were educated about the Pictures in each class session with descriptive text. The study's findings revealed that the students' mean score for the main concept in the pre-test was 21.3. For the supporting details, the pre-test mean score was X1 = 18.7, while the post-test mean score was X2 = 32.2. Based on the results, we can conclude that there was an increase in the students' achieverment score of 4.83 for the main concept and 10.98 for the supporting details, which was higher than the t-table value of 2.080. Based on the results above, it can be said that incorporating pictures of descriptive texts improved the reading comprehension of the grade XI-IPA students at SMA Negeri 1 Remboken.